2014
DOI: 10.3233/jad-140495
|View full text |Cite
|
Sign up to set email alerts
|

Early Neuronal Loss and Axonal/Presynaptic Damage is Associated with Accelerated Amyloid-β Accumulation in AβPP/PS1 Alzheimer's Disease Mice Subiculum

Abstract: The progressive cognitive decline leading to dementia in Alzheimer's disease (AD) patients is the consequence of a severe loss of synapses and neurons affecting particular cell subpopulations in selected brain areas, with the subiculum being one of the earliest regions displaying severe atrophy and pathology. The lack of significant neuronal loss in most AD models is, in fact, the major shortcoming for the preclinical evaluation of drugs that could have greater potential in patients to alleviate or prevent thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 66 publications
12
58
0
Order By: Relevance
“…Our data are consistent with recent reports, which show the geospatial significance of the subiculum in the early onset of AD [26, 34]. The subiculum serves as the major output structure of the hippocampal formation to widespread subcortical and cortical areas [35].…”
Section: Discussionsupporting
confidence: 93%
“…Our data are consistent with recent reports, which show the geospatial significance of the subiculum in the early onset of AD [26, 34]. The subiculum serves as the major output structure of the hippocampal formation to widespread subcortical and cortical areas [35].…”
Section: Discussionsupporting
confidence: 93%
“…We have previously reported that SOM‐positive interneuron population was substantially reduced in the hippocampus and the entorhinal cortex of our APP/PS1 transgenic model at early ages . Thus, we now analyzed the vulnerability of this GABAergic interneuron subset in the perirhinal cortex.…”
Section: Resultsmentioning
confidence: 94%
“…The mechanisms underlying the AD‐associated vulnerability of SOM cells are still unknown, but as we have previously suggested , the extracellular Abeta could be a major factor involved. Thus, as we show in the perirhinal cortex of AD patients and APP/PS1 mice, the loss of SOM neurons is temporally and spatially associated with the amyloid pathology, including the formation of SOM‐positive dystrophies surrounding the Abeta plaques.…”
Section: Discussionmentioning
confidence: 95%
“…1 Although it is not clear whether abnormal processing of the amyloid pre cursor protein (APP) is the initial cause or rather a late event in the pathophysiology of Alzheimer disease, 2 the generation of Aβ from its precursor protein APP induces oxidative stress and plays a critical role in the pathogenesis and advancement of the disease, producing neuronal injury and loss, inflamma tion and characteristic activation of microglia and astrocytic cells. [3][4][5][6] Together with aberrant Aβ deposits in the neuropil, a genetic basis is essential in influencing the onset and/or modifying the progression of the disease. 7 Genomic factors…”
Section: Introductionmentioning
confidence: 99%